Exploring discontinuous intentions of social media users: a cognition-affect-conation perspective - Qaisar, Sara; Nawaz Kiani, Anum; Jalil, Afsheen (Frontiers in Psychology, 2024)
Drawing on the cognition-affect-conation (C-A-C) framework, this study investigates how perceived information, social and system feature overload induce depression and anxiety which leads to affect discontinuous intentions of the social media users. The data collected from 570 social networking site users in China are analyzed through structural equation modeling (SEM).The findings show that perceived information overload, perceived social overload and perceived system feature overload directly affects depression and anxiety among social networking site users, which directly leads to discontinuous intentions. This study fulfills the identified need for an in-depth investigation of discontinuous behavior in social networking sites. The findings provide social networking site providers with guidelines on how to actively manage social networking site user's behavior to reduce the effects of negative emotions on social networking sites.